B. lactis INL1 improves macrophage immune function and modulates events associated with colorectal cancer cell aggressiveness - Carriere, Pedro Matias (2024)
The human milk-derived strain Bifidobacterium animalis subsp. lactis INL1 (B. lactis INL1) (agreement UNS-UNL N°REC-1092496-2) displays properties of a novel probiotic. Previously we showed that in colorectal cancer (CRC) cells, certain probiotics modulate gene expression associated with macrophage activity and that B. lactis INL1 improves macrophage physiology under lipopolysaccharide (LPS) action. Herein we investigate if B. lactis INL1 is able to modulate: 1- the macrophage activity in an inflammatory context and 2- the interaction between macrophages and CRC cells (which are under a pro-tumor factor action). We observed that pretreatment with 5% of cell-free supernatant (CFS) from B. lactis INL1 for 3 h (condition that not affect cell viability) enhances the migratory and phagocytic capacity of RAW264.7 macrophages promoted by LPS exposure for 24 h. Previously we showed that parathyroid hormone-related peptide (PTHrP) is a pro-tumor factor that favors HCT116 cells aggressiveness via E-cadherin deregulation. Also, our in silico analysis revealed that the macrophage inhibitory cytokine GDF15 is overexpressed in HCT116 cells. In view of these findings, we next proceeded to evaluate the expression of both markers. Western blot analysis revealed that the pre-treatment of HCT116 cells with CFS from B. lactis INL1 followed by PTHrP exposition for 24 h reverses the changes in E-cadherin and GDF15 expression induced by PTHrP. Finally, we evaluated whether the conditioned medium from HCT116 cells pre-treated with B. lactis INL1 CFS (MCT-T) and exposed to PTHrP affects macrophage function. Using a viability assay, we observed that MCT-T enhanced macrophage viability compared to conditioned medium from cells under PTHrP action but untreated with probiotic. These results suggest that expression and secretion of GDF15 from tumor cells may mediate the suppressive effects of tumor conditioned medium on immune cells, and that B. lactis INL1 could modulate this process.